Selected works of D. T. Suzuki Volume I : Zen - Suzuki, Daisetz Teitaro; Jaffe, Richard M. (Berkeley, California University of California Press, 2014)
Daisetsu Teitaro Suzuki's writings introduced Buddhism to much of the world outside Asia. The first volume, Zen, presents fourteen writings on Zen Buddhist thought and practice. Evident in these writings is Suzuki's intent to reassert the contemporary relevance of Zen by placing the tradition into conversation with key nineteenth- and twentieth-century intellectual trends.
Keywords: Tham khảo